Proceedings of the 8th ACM Conference on Security &Amp; Privacy in Wireless and Mobile Networks 2015
DOI: 10.1145/2766498.2766519
|View full text |Cite
|
Sign up to set email alerts
|

Security and system architecture: comparison of Android customizations

Abstract: Smartphone manufacturers frequently customize Android distributions so as to create competitive advantages by adding, removing and modifying packages and configurations. In this paper we show that such modifications have deep architectural implications for security. We analysed five different distributions: Google Nexus 4, Google Nexus 5, Sony Z1, Samsung Galaxy S4 and Samsung Galaxy S5, all running OS versions 4.4.X (except for Samsung S4 running version 4.3). Our conclusions indicate that serious security is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Tian et al, (2014) mengekstrak aplikasi dan pustaka prainstal dari image Android kustom, membangun sistem yang cocok dari AOSP, lalu membandingkan aplikasi dan pustaka prainstal untuk menemukan modifikasi dan menilai keamanannya. Penelitian oleh Gallo et al (2015), menyoroti masalah keamanan dalam model izin Android berkaitan dengan kustomisasi Android.…”
Section: Analisis Kredensial Untuk Konfigurasi Keamananan Rom Android...unclassified
“…Tian et al, (2014) mengekstrak aplikasi dan pustaka prainstal dari image Android kustom, membangun sistem yang cocok dari AOSP, lalu membandingkan aplikasi dan pustaka prainstal untuk menemukan modifikasi dan menilai keamanannya. Penelitian oleh Gallo et al (2015), menyoroti masalah keamanan dalam model izin Android berkaitan dengan kustomisasi Android.…”
Section: Analisis Kredensial Untuk Konfigurasi Keamananan Rom Android...unclassified
“…In order to support a functionality, manufacturers might need to modify the standard Android system by embedding support components. However, such customized components often result in vulnerabilities due to incorrect implementation [11,17]. Some previous works have focused on different customized components for vulnerability detection including customized Android phone driver [39], permission re-delegation [16], vendor-specific certification [32], and insecure validation [37].…”
Section: Related Workmentioning
confidence: 99%
“…Another prominent research work analyzes pre-installed apps and reports the presence of known problems such as over-privileged apps, permission redelegation [15], [14]. Gallo et al [16] analyzed five different custom devices and concluded that serious security issues such as poorer permission control grow sharply with the level of customization. More recently, Zhang et al analyzed ION related vulnerabilities caused by the customization it undergoes through different devices [35].…”
Section: Related Workmentioning
confidence: 99%